2013
DOI: 10.1097/tp.0b013e3182782fc1
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance Induction in HLA Disparate Living Donor Kidney Transplantation by Donor Stem Cell Infusion

Abstract: Background We recently reported that durable chimerism can be safely established in mismatched kidney recipients through nonmyeloablative conditioning followed by infusion of a facilitating cell (FC)-based hematopoietic stem cell transplant termed FCRx. Here we provide intermediate-term follow-up on this phase 2 trial. Methods Fifteen HLA mismatched living donor renal transplant recipients underwent low intensity conditioning (fludarabine, cyclophosphamide, 200cGyTBI), received a living donor kidney transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(59 citation statements)
references
References 25 publications
1
58
0
Order By: Relevance
“…These data collectively suggest that donorderived hematopoietic cells are necessary to maintain clonal anergy. Indeed, seminal works for clinical application of hematopoietic chimerism in humans have shown that the presence of macrochimerism was the most reliable predictor for establishment of tolerance (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…These data collectively suggest that donorderived hematopoietic cells are necessary to maintain clonal anergy. Indeed, seminal works for clinical application of hematopoietic chimerism in humans have shown that the presence of macrochimerism was the most reliable predictor for establishment of tolerance (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Although many tolerance induction protocols have been successfully developed in laboratory animals, only a few, using hematopoietic cell transplantation to induce chimerism and tolerance have been applied to clinical trials (16). The conditioning regimen of total lymphoid irradiation (TLI) used with the T cell depletive reagent, anti-thymocyte globulin/serum (ATG/ATS), has been shown to induce tolerance in mice and humans after the development of persistent mixed chimerism (3, 4, 710).…”
Section: Introductionmentioning
confidence: 99%
“…The conditioning regimen at NMH consisted of pre-transplant fludarabine, pre- and post-transplant cyclophosphamide, and 200 cGy total body irradiation. Eight of 15 HLA mismatched patients who underwent this protocol developed high-level (>90%) durable donor chimerism beginning 1 month after transplantation [23]. One patient developed atypical viral infection and bone marrow failure at 3 months post-transplant, which was rectified by infusion of autologous stem cells.…”
Section: Chimerism In Human Kidney Transplantationmentioning
confidence: 99%
“…Durable mixed chimerism was noted in two patients. Three patients in the protocol had only transient donor chimerism lasting several months (2 had reduced doses of FCRx and 1 was highly sensitized with high PRA at the time of transplantation) but in vitro proliferative assay by MLR and CML also demonstrated DSH despite the loss of chimerism [23]. One of them was subsequently withdrawn from MMF and later Tacrolimus based on the in vitro testing, but later developed subclinical Banff 1A rejection in the 12-month protocol biopsy, which was treated successfully with intravenous corticosteroids and by increasing tacrolimus dosage to therapeutic range.…”
Section: Chimerism In Human Kidney Transplantationmentioning
confidence: 99%